2021
DOI: 10.3329/bjms.v20i2.51548
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cyriax Physiotherapy versus Cyriax and low level Laser Therapy on pain and grip strength in Lateral Epicondylitis

Abstract: Objective: The study was designed to evaluate the efficacy of Cyriax physiotherapy versus Cyriaxand Low Level Laser Therapy to compare these techniques in reducing pain and improving gripstrength in patients with lateral epicondylitis. Methodology: The study population included 30patients of lateral epicondylitis (signs and symptoms present for more than 6 weeks) diagnosedin outpatient and indoor facilities of MM Hospital, Mullana. The subjects were selected bymeans of simple random sampling. After fulfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…25 Another study found that; patients with lateral epicondylitis gain significantly more with cyriax physiotherapy combined with low level laser therapy than from cyriax physiotherapy alone during a three-week period. 26 It is evident from these studies that the optimal effective parameters of LLLT for MPS were not yet known. There are a wide range of LLLT protocols with different parameters, wavelengths, powers, doses, duration and depth of the trigger points, which could attribute to these differences in laser therapy effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…25 Another study found that; patients with lateral epicondylitis gain significantly more with cyriax physiotherapy combined with low level laser therapy than from cyriax physiotherapy alone during a three-week period. 26 It is evident from these studies that the optimal effective parameters of LLLT for MPS were not yet known. There are a wide range of LLLT protocols with different parameters, wavelengths, powers, doses, duration and depth of the trigger points, which could attribute to these differences in laser therapy effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The therapist used one hand to support the patient's pronated and wrist fully flexed, while the other hand was, put on the olecranon. The therapist administered a thrust of low-amplitude and high velocity at the end range of elbow extension at the same time maintaining complete wrist flexion and pronation [17,18] (Fig. 3)…”
Section: Treatmentmentioning
confidence: 99%
“…Lateral epicondylitis, commonly called "tennis elbow", is an overuse injury to the wrist extensor that causes inflammation resulting in degenerative changes such as tendinosis and micro-tearing (small tears) in fibrous tissue. 1 Lateral epicondylitis is determined to have a relatively constant annual incidence of around 15.1 cases per 10.000 patients in the United States. The general population prevalence of lateral epicondylitis is reported to be 1% to 3%.…”
Section: Introductionmentioning
confidence: 99%
“…3 Pain around the lateral elbow is known by various names, periostitis, extensor carpi radialis brevis (ECRB) tendinosis, epicondylgia, tennis elbow and lateral epicondylitis. 1 The main goals in the management of lateral P-ISSN: 2830-6317 epicondylitis are pain relief, inflammation and microbleeds, rehabilitation, and prevention of recurrence. 1,3…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation